Membership has its privileges: the effect of membership in international organizations on FDI - Dreher, Axel; Mikosch, Heiner; Voigt, Stefan (World development, 2015)
We argue that membership in specific international organizations (IOs) is an important determinant of foreign direct investment (FDI) inflows. To the extent that membership restricts a country from pursuing policies that are harmful to investors, it can signal reduced political risk. Using data over the 1971-2012 period, we find that membership in IOs does indeed increase inflows of FDI. We find this effect to be substantively important and robust to controlling for alternative determinants of FDI, to using different model specifications and to using an indicator of membership in regional rather than global IOs.
Available online: 1 October 2014
Gesehen am 29.06.2020
Keywords: 1971-2005